Forward Curvatures on Time Scales - M. S. Seyyidoglu; Y. Tunçer; D. Uçar; M. K. Berktaş; V. F. Hatipoğlu (Abstract and Applied Analysis)
We also introduce forward curvature of a curve and give some formulas to calculate forward curvature of a curve on time scales which may be an arbitrary closed subsets of the set of all real numbers. We also introduce the length of a curve parametrized by a time scale parameter in ℝ3.